A review of implantable pulsatile blood pumps: Engineering perspectives. Issue 9 (September 2020) - Wu, Tingting; Khir, Ashraf W; Kütting, Maximilian; Du, Xinli; Lin, Hao; Zhu, Yuxin; Hsu, Po-Lin
It has been reported that long-term use of continuous-flow mechanical circulatory support devices (CF-MCSDs) may induce complications associated with diminished pulsatility. Pulsatile-flow mechanical circulatory support devices (PF-MCSDs) have the potential of overcoming these shortcomings with the advance of technology. In order to promote in-depth understanding of PF-MCSD technology and thus encourage future mechanical circulatory support device innovations, engineering perspectives of PF-MCSD systems, including mechanical designs, drive mechanisms, working principles, and implantation strategies, are reviewed in this article. Some emerging designs of PF-MCSDs are introduced, and possible elements for next-generation PF-MCSDs are identified.